1992
DOI: 10.1164/ajrccm/146.6.1559
|View full text |Cite
|
Sign up to set email alerts
|

Metered-Dose Inhaler Adherence in a Clinical Trial

Abstract: We studied patterns of inhaler usage in a sample of participants from two centers in the Lung Health Study clinical trial. The inhaler, containing either ipratropium bromide or a placebo, was prescribed to be taken as two inhalations three times daily. For 4 months we recorded adherence by both self-report (n = 95) and canister weight change (n = 70). We compared these results with data obtained from a microprocessor monitoring device, the Nebulizer Chronolog (NC), which records the date and time of each inhal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
153
1
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(167 citation statements)
references
References 7 publications
9
153
1
4
Order By: Relevance
“…Although the Medication Adherence Scale used in the study has been shown to be reliable and valid, the authors of many studies have documented the tendency for patients to overestimate their adherence, and we did not use an electronic doser to validate parent-reported adherence. 9,28 Our adherence scores were high and may have overestimated actual adherence. In addition, we only collected data 1 year after the start of CAM therapy.…”
Section: Limitationsmentioning
confidence: 87%
“…Although the Medication Adherence Scale used in the study has been shown to be reliable and valid, the authors of many studies have documented the tendency for patients to overestimate their adherence, and we did not use an electronic doser to validate parent-reported adherence. 9,28 Our adherence scores were high and may have overestimated actual adherence. In addition, we only collected data 1 year after the start of CAM therapy.…”
Section: Limitationsmentioning
confidence: 87%
“…The possibility that the actual number of remaining doses overestimates drug adherence ("clicking" the inhaler without inhaling) cannot be ruled out. This kind of overuse or "test firing" has been shown by others with the use of an electronic medication monitor in the inhaler [5,8]. This electronic instrument cannot confirm that the medication was inhaled or used correctly, but only when and how often the inhaler was actuated.…”
Section: Discussionmentioning
confidence: 98%
“…This has been performed using an electronic inhaler timer device (Nebulizer Chronolog; Forefront Technologies Inc., Lakewood, CO, USA), and has repeatedly shown that adherence to asthma medication is generally poor. These studies show that only about 50±77% of the medication is used as prescribed by the doctor [3±6], and that when asked, patients overestimate the use of their own medication 50±90% of the time [3,7,8]. Poor compliance with prescribed therapy can lead to difficulties in assessing disease severity as the expected effect of the treatment given is missing, which may in fact influence the clinician in changing to a different, and sometimes a more complicated treatment regimen instead of focusing on improving the patient compliance.…”
mentioning
confidence: 99%
“…Additionally, the adherence literature has noted a tendency for patients to generally overestimate adherence in using medications. 27,28 A more systematic analysis of specific adherence behaviors, particularly related to the use of medications, may yield an even higher rate of nonadherence in sickle cell.…”
Section: Discussionmentioning
confidence: 99%